Synthesis of 3-acylindoles by oxidative rearrangement of 2-aminochalcones using a hypervalent iodine reagent and cyclization sequence. Issue 32 (27th July 2017) - Nakamura, Akira; Tanaka, Satoshi; Imamiya, Akira; Takane, Reo; Ohta, Chiaki; Fujimura, Kazuma; Maegawa, Tomohiro; Miki, Yasuyoshi
Abstract : An efficient one-pot 3-acylindole synthesis by oxidative rearrangement of 2-aminochalcones and sequential cyclization has been developed. Abstract : An efficient one-pot method was developed for the construction of 3-acylindoles via oxidative rearrangement of 2-aminochalcones followed by intramolecular cyclization. The reaction was used to convert a variety of 2-aminochalcones into 3-acylindoles in moderate to high yields.